2020
DOI: 10.7717/peerj.8880
|View full text |Cite
|
Sign up to set email alerts
|

A new insect trackway from the Upper Jurassic—Lower Cretaceous eolian sandstones of São Paulo State, Brazil: implications for reconstructing desert paleoecology

Abstract: The new ichnospecies Paleohelcura araraquarensis isp. nov. is described from the Upper Jurassic-Lower Cretaceous Botucatu Formation of Brazil. This formation records a gigantic eolian sand sea (erg), formed under an arid climate in the south-central part of Gondwana. This trackway is composed of two track rows, whose internal width is less than one-quarter of the external width, with alternating to staggered series, consisting of three elliptical tracks that can vary from slightly elongated to tapered or circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…However, what can be confidently stated is that it is already recognized that dune facies are host to mammal/mammaloid and arachnid trackway assemblages, and variously labeled ichnocoenoses include the Permian Chelichnus and longer-ranging Octopodichnus ichnocoenoses, subsumed in the eponymous Chelichnus and Octopodichnus ichnofacies, respectively. At the time of writing, the Octopodichnus ichnofacies is ostensibly recognized from the Permian to Recent (Lockley et al, 1994; Lockley, 2004; Hunt and Lucas, 2007; Krapovickas et al, 2016; Peixoto et al, 2020), an inference consistent with the Waenhuiskrans Formation assemblage reported here (Fig. 12).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, what can be confidently stated is that it is already recognized that dune facies are host to mammal/mammaloid and arachnid trackway assemblages, and variously labeled ichnocoenoses include the Permian Chelichnus and longer-ranging Octopodichnus ichnocoenoses, subsumed in the eponymous Chelichnus and Octopodichnus ichnofacies, respectively. At the time of writing, the Octopodichnus ichnofacies is ostensibly recognized from the Permian to Recent (Lockley et al, 1994; Lockley, 2004; Hunt and Lucas, 2007; Krapovickas et al, 2016; Peixoto et al, 2020), an inference consistent with the Waenhuiskrans Formation assemblage reported here (Fig. 12).…”
Section: Discussionsupporting
confidence: 83%
“…Presently, given that the Chelichnus ichnofacies sensu Hunt and Lucas (2007, 2016) is defined on the basis of tetrapod tracks as limited to the Permian through Lower Jurassic, and the Octopodichnus ichnofacies, also defined by various authors (see Krapovickas et al, 2016) as ranging from Permian to Recent, we are left to ponder the relationships and appropriate ichnocoenoses and ichnofacies labels applicable to Cretaceous through Cenozoic dune ichnofaunas. For example, Peixoto et al (2020) noted that the occurrence of traceways like Octopodichus helps trace continuity between Paleozoic and post-Paleozoic ichnofaunas, at least in the sense of the eponymous Octopodichnus ichnofacies, when regarded as an ‘invertebrate’ ichnofacies recognized independently of tetrapod traces. The extent to which different ichnofaunas, including their tetrapod components, might be considered representative of different dune/desert paleoenvironments (e.g., with different precipitation regimes) is open to discussion, as noted by Krapovickas et al (2016), and naturally involves wide-ranging and complex consideration of paleoenvironmental and paleobiological evolution in space and time (e.g., Buatois and Mángano, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current record of fossil woods, added to the previously mentioned findings that include fossil remains and traces of vertebrates and invertebrates, together with fossil plants and palynomorphs, support the existence of humid and certainly stable marginal environments similar to an oasis that would allow maintaining this important biota in the Botucatú Desert (Almeida, 1950;Suguio & Coimbra, 1972;Mussa, 1974;Herbst & Ferrando, 1985;Martínez & Figueiras, 1991;Martínez et al, 1993;Würdig & Pinto, 2001;Shen et al, 2004;Leonardi et al, 2007;Perea et al, 2009;Pires et al 2011;Mesa, 2012;De Valais et al, 2012;Buck et al, 2017, Santa Cruz et al, 2019Peixoto et al, 2020). These records added to the role of these wetlands/paleoerg as biogeographical bridges/barriers (Gallego & Rinaldi, 2004) that facilitated the colonization and dispersion of this flora and fauna, open an interesting future panorama to continue analyzing different aspects of these important geological sections of the Late Jurassic-Early Cretaceous from South America.…”
Section: Discussionmentioning
confidence: 95%
“…These Mesozoic eolian outcrops have a diverse fossil record recorded in different localities of South America such as petrified logs (Suguio & Coimbra, 1972;Mussa, 1974;Pires et al, 2011), palynomorphs (Santa Cruz et al, 2019, vertebrates (Leonardi et al, 2007;Perea et al, 2009;Mesa, 2012;De Valais et al, 2012), invertebrate footprints (Buck et al, 2017;Peixoto et al, 2020), bivalve molluscs (Martínez & Figueiras, 1991;Martínez et al, 1993), and crustaceans (Almeida, 1950;Würdig & Pinto, 2001;Herbst & Ferrando, 1985;Shen et al, 2004).…”
Section: The Solari/botucatú Formationmentioning
confidence: 99%
“…This distinctive layout is unlike that of SGDS 1290. De Peixoto et al (2020) attributed traces lacking a medial impression and comprising closely appressed pairs or triplets of mostly elliptical tracks from the Upper Jurassic or Lower Cretaceous of Brazil to a new ichnospecies of Paleohelcura and attributed them to a pterygote insect track maker. Tracks in this ichnospecies are arranged in rows oriented oblique to the trackway axis, and track sets in this ichnospecies lie close to the midline.…”
Section: Methodsmentioning
confidence: 99%